Social risks of e-learning in a digital society - E. V. Chmykhova (Цифровая социология)
The concepts of the essence of social risks in the digital society, as well as their specifics in the process of e-learning have been clarified in the article materials. The importance of conducting research in this field, which is dynamically developing on the basis of digital technologies, – has been argued. The classification of scientific works in the field of studying the risks of e-learning on the basis of socio-technological, institutional and General social approaches has been given. A justification for the institutional nature of social risks of e-learning, as well as the grounds for classification by forms of manifestation, levels and sources of occurrence, as well as organizational and technological characteristics has been provided. To identify the essence of these risks, the concept of S.A. Kravchenko’s “humanistic theory of a complex society”, which has a nonlinear dynamics of development, – has been proposed. The concept of types and types of social risks in the field of this form of education has been introduced. The characteristic of risk types has been made in relation to such characteristics of modern society as the complexity of self-organization processes, the open nature and non-linearity of transformation processes.The understanding of various types of risks has been explained, that are associated with the problems of implementing the goals of humanistic educational policy; incomplete integration of methodological tools for e-learning; the break in educational traditions; conflicts between subjects of educational relations; the lack of adaptability of digital technologies to the content of social interaction; the complexity of the nature of distance learning technologies in the modern supercomplex socio-global system; impact on the formalization of learning new types of rationality; objectively inherent in modern society’s global social risks; conflicts of social movements with the interests of the subjects realizing the functions of education; with the indivisibility of the security of complex society in different spheres and levels of social interaction. Ways to manage e-learning risks have been described.